Photophysics of charge transfer complexes formed by tetracene and strong acceptors - Theurer, Christoph P.; Valencia, Ana M.; Hausch, Julian; Zeiser, Clemens; Sivanesan, Vipilan; Cocchi, Caterina; Tegeder, Petra; Broch, Katharina (The journal of physical chemistry. C, Energy, materials, and catalysis, 2021)
Organic charge transfer complexes (CTCs) with near-infrared absorption received growing interest in the past years, but the details of their photophysics, especially in thin films, remain largely unknown. We combined experimental and computational methods to thoroughly investigate and compare CTCs formed by tetracene with 2,2′-(perfluoronaphthalene-2,6-diylidene)dimalononitrile and 2,3,5,6-tetrafluoro-7,7,8,8,-tetracyanoquinodimethane, respectively. Using ultrafast transient absorption spectroscopy, the photophysics of these small bandgap CTCs was revealed, which is dominated by a sub-picosecond relaxation of the excitons back to the ground state. In equimolar blends, tetracene singlet fission is suppressed while in blends with excess of tetracene reduced lifetimes of tetracene, singlet and triplet excitons were found.